Fate of β-Carotene within Loaded Delivery Systems in Food: State of Knowledge - Vaibhav Kumar Maurya; Amita Shakya; Manjeet Aggarwal; Kodiveri Muthukaliannan Gothandam; Torsten Bohn; Sunil Pareek (MDPI AG, 2021)
Nanotechnology has opened new opportunities for delivering bioactive agents. Their physiochemical characteristics, i.e., small size, high surface area, unique composition, biocompatibility and biodegradability, make these nanomaterials an attractive tool for β-carotene delivery. Delivering β-carotene through nanoparticles does not only improve its bioavailability/bioaccumulation in target tissues, but also lessens its sensitivity against environmental factors during processing. Regardless of these benefits, nanocarriers have some limitations, such as variations in sensory quality, modification of the food matrix, increasing costs, as well as limited consumer acceptance and regulatory challenges. This research area has rapidly evolved, with a plethora of innovative nanoengineered materials now being in use, including micelles, nano/microemulsions, liposomes, niosomes, solidlipid nanoparticles, nanostructured lipids and nanostructured carriers. These nanodelivery systems make conventional delivery systems appear archaic and promise better solubilization, protection during processing, improved shelf-life, higher bioavailability as well as controlled and targeted release. This review provides information on the state of knowledge on β-carotene nanodelivery systems adopted for developing functional foods, depicting their classifications, compositions, preparation methods, challenges, release and absorption of β-carotene in the gastrointestinal tract (GIT) and possible risks and future prospects.